2020
DOI: 10.7150/ijms.43272
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of DNA methylation-driven genes for the prognosis of lung squamous cell carcinoma using MethylMix

Abstract: Background: DNA methylation acts as a key component in epigenetic modifications of genomic function and functions as disease-specific prognostic biomarkers for lung squamous cell carcinoma (LUSC). This present study aimed to identify methylation-driven genes as prognostic biomarkers for LUSC using bioinformatics analysis. Materials and Methods: Differentially expressed RNAs were obtained using the edge R package from 502 LUSC tissues and 49 adjacent non-LUSC tissues. Differentially methylated genes were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…DDX47 is involved in maintenance of genome stability via interacting with FANCD2 to lower R-loop levels [28], and study has revealed that overexpression of DDX47 induces tumor cells apoptosis [29]. DQX1, acting as the methylation-driven genes, is a novel prognostic marker in lung squamous cell carcinoma [30]. EXOSC5 could promotes growth of colorectal cancer through regulating ERK and AKT pathways [31].…”
Section: Discussionmentioning
confidence: 99%
“…DDX47 is involved in maintenance of genome stability via interacting with FANCD2 to lower R-loop levels [28], and study has revealed that overexpression of DDX47 induces tumor cells apoptosis [29]. DQX1, acting as the methylation-driven genes, is a novel prognostic marker in lung squamous cell carcinoma [30]. EXOSC5 could promotes growth of colorectal cancer through regulating ERK and AKT pathways [31].…”
Section: Discussionmentioning
confidence: 99%
“…CYP1B1-AS1 has been confirmed to play an important role in triple-negative breast cancer, lung adenocarcinoma and acute myeloid leukemia, and was associated with the prognosis of these cancers ( Cheng et al, 2021 ; Ren et al, 2021 ; Vishnubalaji and Alajez, 2021 ). Abnormal methylation and low expression of CTC-523E23 led to poor prognosis in patients with lung squamous cell carcinoma ( Rui Li et al, 2020 ). Inhibition of LINC01010 may promote the migration and invasion of lung cancer cells ( Cao et al, 2020 ) and help in the prediction of neuroblastoma prognosis ( Gao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Cox regression model was used to further analyze the predictive genes screened by the linear mixed model and to explore the relationship between methylation-driven genes and the prognosis of LUAD [ 36 ]. It is still assumed that all the markers may be involved in the development of LUAD, and the effect size of each gene should follow a normal distribution: …”
Section: Methodsmentioning
confidence: 99%